A Designing Model System for Identification Violation of the Law Using Web Crawling and Text Mining - Faried, Isnin; Atmodjo W.P, Dwi; Tampubolon, Lely P.D. (ADPEBI, 2022)
This study aims to create a model of an opinion detection system that will be used as a system to prevent violations of the ITE Law. Source of opinion from Indonesian-language twitter. The system was developed using web crawler technology and text mining with the implementation of one of the classification methods. This means that the research does not focus on sentiment analysis. A web crawler with a focused crawling algorithm can make it easier to find legal sources that are used as guidelines for identifying violations from a user's opinion. The source of law in question is the ITE Law. The resulting convenience is being able to compile document sources on only specific topics and crawl relevant areas of the web. The resulting impact can reduce the amount of network traffic, resulting in significant savings in hardware and network resources. Opinion Mining in this research uses the Naïve Bayes Multinominal Text (NBMT) algorithm. This algorithm is one of the algorithms in accordance with the opinion classification of twitter, capable of producing good accuracy. Another result obtained from the implementation of the NBMT algorithm is the speed of the process in the opinion classification process. The resulting model is used as an alternative that can be used to prevent opinions that have potential violations, especially the ITE Law. To be more perfect, the author plans to develop research that focuses on opinion mining which has better accuracy, especially the detection of violations of the ITE Law. Keywords : Model System, Violation the ITE Law, Focused Web Crawling, Text Mining